Baabwaa & Wooliam - Elliott, David, 1947-; Sweet, Melissa, 1956- (Somerville, Massachusetts : Candlewick Press, 2017)
Baabwaa and William are friends, and together they decide to have an adventure of their own. After meeting a fierce wolf in sheep's wool they form an unusual friendship with the wolf, teaching him to read and knit. They also lose a little weight.
Keywords: Friendship -- Juvenile fiction; Sheep -- Juvenile fiction; Knitting -- Juvenile fiction; Wolves -- Juvenile fiction; Friendship -- Fiction; Sheep -- Fiction; Knitting -- Fiction; Wolves -- Fiction; Wolves. -- Juvenile fiction; Wolves. -- Fiction